Markets for environmental protection: design and performance - Montero, Juan Pablo (Estudios de Economía, 2016)
Policy makers in different parts of the world are paying more attention to environmental markets (i.e., tradeable permits markets) as an alternative to the traditional command-and-command control approach of setting uniform emission and technology standards. I extend the basic (perfect information) model of a permits market to accommodate for practical considerations including regulator’s asymmetric information on firms’ costs, uncertainty on benefits from pollution control, incomplete enforcement, incomplete monitoring of emissions and the possibility of voluntary participation of non-affected sources. Implications for instrument design and implementation are provided.